Solving Economic Dispatch Problems Utilizing Cuckoo Search Algorithm - M. H., Sulaiman; Mohd Rusllim, Mohamed (2014)
This paper presents one of the latest nature-inspired meta-heuristics algorithms, namely Cuckoo Search (CS) algorithm to solve economic dispatch (ED) problems in power system. In order to obtain as close as to practical system, the effect of valve-loading effects together with the other constraints such as ramp rate limits, prohibited operating zones as well as generators operating limits have been taken into consideration in solving the most complex optimization problem. To show the effectiveness of proposed CS in solving ED problem, two test systems are utilized: TAIPOWER 40-units and 15-units systems and then the performance of proposed CS will be compared to the other recent techniques.